Water and beverage consumption among children aged 4–13 years in France: analyses of INCA 2 (Étude Individuelle Nationale des Consommations Alimentaires 2006–2007) data. Issue 13 (16th February 2016) - Vieux, Florent; Maillot, Matthieu; Constant, Florence; Drewnowski, Adam
Abstract: Objective: To examine the consumption of plain water among children in France and compare total water intakes with guidelines issued by the European Food Safety Authority (EFSA). Design: Nationally representative data were used to assess food, beverage and water consumption by sex, age group (4–8 years, 9–13 years), income-to-poverty ratio, eating occasion and location. Beverages were classified into nine groups: water (tap or bottled), milk, 100 % fruit juice, sodas, fruit drinks, hot beverages, sports drinks and flavoured waters. Total water volume in relation to energy intake (litres/kcal) was also examined. Setting: INCA 2 study (Étude Individuelle Nationale des Consommations Alimentaires 2006–2007). Subjects: French children ( n 835) aged 4–13 years. Results: Total water intakes were accounted for by plain water (34 %), beverages (26 %) and food moisture (40 %). Plain water could be tap (18 %) or bottled (16 %). Older children drank more plain water than did younger children and boys drank more plain water than did girls. No socio-economic gradient for plain water consumption was observed. About 90 % of children did not meet the EFSA water intake recommendations. The daily water shortfall ranged from 367 to 594 ml/d. Water-to-energy ratio was 0·75–0·77 litres/1000 kcal (4184 kJ). Children drank milk at breakfast and plain water during lunch and dinner. Caloric beverages provided 10 % of dietary energy; consumption patterns varied by eating location. Conclusions: Total water intakes among young children in France were below EFSA-recommended levels. Analyses of beverage consumption patterns by eating occasion and location can help identify ways to increase water consumption among children.